Effects of Incorporated Rye and Hairy Vetch Cover Crop Residue on the Persistence of Weed Seeds in the Soil. Issue 3 (7th February 2018) - Mohler, Charles L.; Taylor, Alan G.; DiTommaso, Antonio; Hahn, Russell R.; Bellinder, Robin R.
Abstract: Incorporation of cover crop residue into the soil has been suggested as a means for reducing weed seedbanks. To explore this hypothesis, we buried mesh bags of seeds mixed with sand at 15-cm depth in late fall in plots that had been planted with rye ( Secale cereale L.) or hairy vetch ( Vicia villosa Roth.) or left unplanted. Separate bags contained either velvetleaf ( Abutilon theophrasti Medik.), giant foxtail ( Setaria faberi Herrm.), Powell amaranth ( Amaranthus powellii S. Watson), or common lambsquarters ( Chenopodium album L.). The experiment used a randomized complete block design with five replications, and enough bags were buried to allow a final recovery in each of the following three springs. Each spring, bags were exhumed, and seeds were either counted and tested for viability or mixed with chopped cover crop material or simply stirred for control bags, and the material was reburied. The experiment was completed twice with initial burials in fall of 2011 and 2013. Rye had no consistent effect on persistence of seeds of any of the species. For two observation intervals, rye increased persistence of a species; for another two intervals, it decreased persistence relative to the control; but mostly rye did not affect persistence. Hairy vetch decreased persistence of C. album and A. powellii in both runs of the experiment but had no effect on persistence of A. theophrasti and S. faberi . Germination of the first two species is promoted by nitrate, whereas A. theophrasti germination is not sensitive to nitrate, and S. faberi is only rarely nitrate sensitive. We suggest that nitrate released during decomposition of hairy vetch may have promoted fatal germination of C. album and A. powellii . Incorporation of legume cover crops like hairy vetch may provide a means for decreasing the seedbanks of the many weed species whose germination is promoted by nitrate. The lack of any reduction of A. theophrasti and S. faberi seed persistence in response to hairy vetch and the inconsistent and mostly negligible effect of rye indicate that a general increase in readily decomposable organic matter through incorporation of cover crops may be ineffective at reducing weed seedbanks.